PERSEPSI DAN PERILAKU KONSERVASI LAHAN PADA BERBAGAI KEMIRINGAN DAN DAMPAKNYA PADA PRODUKSI USAHATANI SAYURAN: STUDI KASUS DI KABUPATEN REJANG LEBONG PROVINSI BENGKULU - Sumantri, Bambang; Sukiyono, Ketut (Bumi Lestari Journal of Environment; Vol 11 No 1 (2011), 2011)
This research was aimed to examine the perception of vegetable farmers on land conservation and investigating the impact of their perception and behavior toward land conservation on production. This research was conducted in Rejang Lebong District. On this research one hundred fifteen of respondents were selected as sample. Data collected by using stratified random sampling technique based on their land slope. Analytical descriptive method and double log models were used to analyze data which gathered from face to face interview guided by questionnaire. The result of the research showed that vegetable farmers had positive perception on land conservation. Their positive perception were reflected by their action in conserving their land, whether by bench terrace development or growing cover trees. The research also found that all variables included in the model had an expected sign, i.e., positive, except for cover trees growing and seed application that had negative sign. However, not all of these variables were different from zero. Only the cost of terrace development variable, fertilizer usage, land area, education, and farmer motivation to conserve their land had significant factors in influencing vegetable production, while farmers perception were not influenced.
Keywords: land conservation; farmer perception; farmer behaviour